2011
DOI: 10.1155/2011/615032
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a Phosphate‐Solubilizing Halophilic Bacterium Kushneria sp. YCWA18 from Daqiao Saltern on the Coast of Yellow Sea of China

Abstract: Phosphate-solubilizing bacteria (PSB) function in soil phosphorus cycle, increasing the bioavailability of soil phosphorus for plants. Isolation and application of salt-tolerant or halophilic PSB will facilitate the development of saline-alkali soil-based agriculture. A moderately halophilic bacterium was isolated from the sediment of Daqiao saltern on the eastern coast of China, which also performs phosphate-solubilizing ability. The bacterium was assigned to genus Kushneria according to its 16S rRNA gene seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
113
3
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(131 citation statements)
references
References 41 publications
3
113
3
12
Order By: Relevance
“…(Wani et al 2005), Azotobacter (Kumar et al 2001), Xanthomonas (De Freitas et al 1997), Enterobacter, Pantoea, andKlebsiella (Chung et al 2005). Several halophilic bacteria Kushneria sinocarni have also been isolated from the sediment of Daqiao saltern on the eastern coast of China, which may be useful in stress conditions; salt affected agricultural soils (Zhu et al 2011). Among the whole microbial population in soil, PSB constitute 1 to 50 %, while phosphorus solubilizing fungi (PSF) are only 0.1 to 0.5 % in P solubilization potential (Chen et al, 2006) which includes Penicillium and Aspergillus, Rhizoctonia solani, Trichoderma.…”
Section: Phosphate Solubilizing Micro-organismsmentioning
confidence: 99%
“…(Wani et al 2005), Azotobacter (Kumar et al 2001), Xanthomonas (De Freitas et al 1997), Enterobacter, Pantoea, andKlebsiella (Chung et al 2005). Several halophilic bacteria Kushneria sinocarni have also been isolated from the sediment of Daqiao saltern on the eastern coast of China, which may be useful in stress conditions; salt affected agricultural soils (Zhu et al 2011). Among the whole microbial population in soil, PSB constitute 1 to 50 %, while phosphorus solubilizing fungi (PSF) are only 0.1 to 0.5 % in P solubilization potential (Chen et al, 2006) which includes Penicillium and Aspergillus, Rhizoctonia solani, Trichoderma.…”
Section: Phosphate Solubilizing Micro-organismsmentioning
confidence: 99%
“…Phosphate-solubilizing bacteria (PSB) play a crucial role in soil P solubilization (Abd-Alla 1994), increasing the bioavailability of soil P for plants (Zhu et al 2011). PSB can transform insoluble P to available P in the soil, so as to improve fertilizer use efficiency and crop yield (Hao et al 2006;Jiang et al 2012;Hu et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Though, there are some information regarding the stress tolerant PSMs such as Rhodotorula sp., PS4 is highly tolerant to temperature, pH and salt variations (Mundra et al, 2011); Kushneria sp. YCWA18 is tolerant to salt conditions (Zhu et al, 2011); Bacillus megatherium is tolerant to salt conditions (Xiang et al, 2011); Burkholderia vietnamiensis M6 is tolerant to temperature, pH and salt conditions (Park et al, 2010), and Pantoea agglomerans R-42 is tolerant to temperature, pH and salt conditions (Sharan et al, 2008;Son et al, 2006); most of the previously isolated PSMs are reported to perform poorly under stress conditions making them less appropriate for such environments. In this context, PSMs with the genetic potential for increasing tolerance to high temperature, pH and high salt concentration are still considered to be important for the establishment, multiplication and production of environmentally friendly bio-inoculants.…”
Section: Introductionmentioning
confidence: 99%